Determination of environmental load factors for ISO 19902 code in offshore Malaysia using FORM structural reliability method - Nizamani, Z. (Elsevier Ltd, 2014)
Environmental load factor, used for the design of Jacket platform design in Malaysia, are based on calibration of platforms located in Gulf of Mexico and North Sea. This load factor is assumed to be high for locations where moderate climate governs i.e. regions lying near equator like Malaysia which is at 7Â° north of the equator. For Jacket platforms, safety can be achieved by taking into consideration of hazards produced by rare events of wave, wind and current. Environmental loads are not like live loads acting on land-based structure but are more severe due to unpredictable weather conditions. These environmental loads can act with unexpected severity on offshore structures. Material strength of tubular components and joints plays significant role against risk. The resistance can also be reduced because of damage to Jacket, continuous action of wave forces causing fatigue and corrosion. Four platforms from three different regions of Malaysia were selected for the reliability analysis. Probabilistic techniques were used to evaluate and estimate the load and resistance uncertainty. FORM method of reliability was used for structural reliability analysis of Jackets. Modified environmental load factor is proposed for offshore Malaysia considering component, joint and system reliability analysis based on calibration. Â© 2014 Elsevier Ltd.